Hydrogen adsorption on Na and Li decorated WTe2. (10th April 2019) - Sarvazad, Khatereh; Elahi, Mohammad; Ahmadian, Farzad; Boochani, Arash
Abstract: In this paper, we investigate the effect of adsorption of hydrogen on the surface of the WTe2 that decorated with Na and Li. The first principle calculations based on the density functional theory showed that due to the larger energy of the sodium and lithium atoms on the WTe2 surface relative to the cohesive energy of these atoms in bulk, Li and Na atoms can be as a single atom on the surface of the WTe2 not as clusters atoms. By decoration of WTe2 with Na and Li atoms the structures can be behavior as metal. By absorbing hydrogen molecules on the surface of WTe2, the results show that the Li atom was able to absorb more hydrogen molecules and could be used as a promising candidate in the storage field as well as the hydrogen gas sensor.